From Orality to Scriptuality : the Contribution of African Languages to the English Language Teaching - Andjou Frédéric KOUADIO (Akofena)
Since 1953, UNESCO, in The Use of Vernacular Languages in Education, has officially encouraged mother tongue based education. To make it possible, in 2008 it published a collection of examples which attest to the growing interest in integrating mother tongues in education and explore the wide variety of models, tools and resources which are being tried out to promote teaching programs in mother tongues. The implementation of such a project implies that African languages be teachable in the school institution. To be so, means the move from orality to the scriptuality of languages in Africa where most of them remain non-graphematized. Today’s world is seen as a 'knowledge society' where knowledge has a universal character and is translated in the form of information through languages and by means of information and communication technologies. With the challenges of this world, scriptualizing African languages is no longer an option but rather an obligation. The objective of this study is to highlight the contribution that the transition from orality to the scripturality of languages in Africa can give to teaching in general and to the teaching of the English language in particular. To achieve this objective, we opted for documentary research which made it possible to define a certain number of prerequisites for successful language learning. Based on our prerequisites, the results showed that the scripturality of languages in Africa is a source of input, but also a source of motivation; all things that contribute to the success in learning English.